THE INFLUENCE OF SERVICE QUALITY AND EXPERIENTIAL MARKETING ON CONSUMERS' DECISIONS TO VISIT WARKOP AGAM SETIA BUDI, MEDAN CITY - Melisa Siahaan; Indawati Lestari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article aims to determine and analyze the quality of service towards consumer decisions to visit Warkop Agam Setia Budi. To find out and analyze Experiential Marketing on Consumer Decisions, visit Warkop Agam Setia Budi. To find out and analyze the Quality of Service and Experiential Marketing towards Consumer Decisions to visit Warkop Agam Setia Budi. The type of research used in this study is a quantitative associative research approach . In this study, the population is then drawn conclusions. In this study, the population used is customers or consumers of Warkop Agam. Warkop Agam Setia Budi was established in February 2024 , totaling 10,593 customers and determining the sample using the Slovin formula . This study rounded up the number of samples to 99 respondents. The sampling technique in this study was carried out using non-probability and accidental sampling techniques. Data collection techniques through distributing questionnaires to obtain primary data and documentation to obtain secondary data. The statistical data analysis technique used was multiple linear regression and previously a classical assumption test and validity and reliability instrument test were carried out. As well as determination testing and hypothesis testing. The results of the study indicate that 1) the results of the study indicate that partially the service quality variable (X1) has a positive and significant effect on consumer decisions (Y). 2. the results of the study indicate that partially the experiential marketing variable (X2) has a positive and significant effect on consumer decisions (Y). 3) the results of the study indicate that simultaneously there is a positive and significant effect on the service quality variable (X1) and experiential marketing (X2) on consumer decisions (Y).